Israel, Latin America and the United States: A peripheral-realist perspective - Carlos Escudé (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2009)
This document is the paper-format version of the keynote address delivered by its author on August 2, 2009, to the opening session of the Latin American section (AMILAT) of the 15th World Congress of Jewish Studies, at the Hebrew University of Jerusalem. It attempts to understand the long-term shift towards the worse of Israeli-Latin American relations, which started with an almost unqualified support for the establishment of the State of Israel on the side of both Latin American right-wing governments and left-wing parties and popular organizations, but have been deteriorating ever since. It suggests that this involution can be largely explained in terms of at least four intervening variables: Israel's vulnerability, its special relationship with the United States after 1967, Latin American social structure, and the class identity of the leadership of the Latin American Jewry. It argues that overlooking the peripheral character of Israel in the interstate system has led to distortions in the understanding of Israeli-Latin American relations.
Keywords: 330